Intercultural language teaching and learning - Liddicoat, Anthony; Scarino, Angela (Wiley-Blackwell, 2013)
This wide-ranging survey of issues in intercultural language teaching and learning covers everything from core concepts to program evaluation, and advocates a fluid, responsive approach to teaching language that reflects its central role in fostering intercultural understanding. * Includes coverage of theoretical issues defining language, culture, and communication, as well as practice-driven issues such as classroom interactions, technologies, programs, and language assessment * Examines systematically the components of language teaching: language itself, meaning, culture, learning, communicating, and assessments, and puts them in social and cultural context * Features numerous examples throughout, drawn from various languages, international contexts, and frameworks * Incorporates a decade of in-depth research and detailed documentation from the authors' collaborative work with practicing teachers * Provides a much-needed addition to the sparse literature on intercultural aspects of language education